2006
DOI: 10.1016/j.ijsolstr.2005.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of microstructural strain tensors for granular assemblies

Abstract: The micromechanical interpretation of strain tensor for granular assemblies has been a subject of considerable scientific interest in recent years. This paper gives an overview on 10 different microstructural strain definitions that can be found in the granular mechanics literature. After a theoretical introduction and comparison, the different versions are compared to each other and to the macro-level strain with the help of discrete element simulations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
82
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(99 citation statements)
references
References 11 publications
5
82
0
Order By: Relevance
“…Bagi [13] also observed this effect in 2D simulations of a uniaxial compression test, showing data which Figure 3. Local best-fit strain versus distance from the bottom boundary non-dimensionalized by the mean particle diameter: stress increment 0-1 MPa.…”
Section: Strain Resultsmentioning
confidence: 73%
See 2 more Smart Citations
“…Bagi [13] also observed this effect in 2D simulations of a uniaxial compression test, showing data which Figure 3. Local best-fit strain versus distance from the bottom boundary non-dimensionalized by the mean particle diameter: stress increment 0-1 MPa.…”
Section: Strain Resultsmentioning
confidence: 73%
“…A measure of the internal strain can then be obtained by calculating some deformation gradient. A summary of different proposed methods for strain calculation based on individual particle displacements is given by O'Sullivan et al [12] and Bagi [13]. A few key methods will be mentioned here.…”
Section: Strain Calculationmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the local results are found by looking at particle quantities with respect to their neighboring particles; specifically, the strain in the vicinity of each particle, which is computed using Cundall's best-fit strain [5], which represents the average deformation of a set of points undergoing displacement:…”
Section: Local Behaviormentioning
confidence: 99%
“…There are several methods for transforming between discrete, grainscale parameters and macroscopic, continuum stress and strain (e.g. [31,32]). We consider the pack to be a representative volume of a larger medium, and compute the average stress and strain within this volume as described below.…”
Section: Evaluating Macroscopic Parametersmentioning
confidence: 99%